Informatics in Control, Automation and Robotics: 12th International Conference, ICINCO 2015 Colmar, Alsace, France, 21-23 July, 2015 revised selected papers - Filipe, Joaquim; Gusikhin, Oleg; Madani, Kurosh; Sasiadek, Jurek (Springer International Publishing, 2016)
Text Categorization Methods Application for Natural Language Call Routing -- ECG Signals for Biometric Applications - Are we there yet -- Contactless Thin-Layered Torque Sensor Module with Fully-digital Signal Processing Circuit -- Object Contour Reconstruction using Bio-inspired Sensors -- Sliding Mode Control of Linear Time-varying Systems - Application to Trajectory Tracking Control of Nonlinear Systems -- A Pursuit-evasion Game Between Unmanned Aerial Vehicles -- Means for Finding Meaningful Levels of a Hierarchical Sequence Prior to Performing a Cluster Analysis -- A Multi-layer Approach for Interactive Path Planning Control -- Detection and Tracking of Dynamic Objects using 3D Laser Range Sensor on a Mobile Platform -- A Comparison of General-Purpose FOSS Compression Techniques for Efficient Communication in Cooperative Multi-Robot Tasks -- Enhanced Physical Interaction Performance for Compliant Joint Manipulators using Proxy-based Sliding Mode Control -- Hand-projector Self-calibration Using Structured Light -- Adaptive Embedded Systems - New Composed Technical Solutions for Feasible Low-Power and Real-time Flexible OS Tasks -- Adaptive Control of Position Compensation for Cable-Conduit Mechanisms Used in Flexible Surgical Robots -- Soil Strength-based Estimation of Optimal Control Parameters for Wheeled Robots on Rough Terrain -- Design of Safe Reactional Controller for Chamber Pressure in Climbing Robot CREA.
Description based upon print version of record
Soil Identification and Control-Parameter Estimation for Optimal Driving of Wheeled Robots on Rough Terrain
Keywords: Konferenzschrift